Impact of the Intubation System on Postoperative Foreign Body Sensation Following Lacrimal Surgery - Burghardt, Marie Elisabeth; Dettmer, Wiebke; Chodorowska, Agnieszka; Struck, Hans-Gert; Viestenz, Arne; Heichel, Jens (Klinische Monatsblätter für Augenheilkunde, 2025)
Background Monocanalicular intubation systems such as Mini-Monoka and Monoka are well established in the treatment of adult patients with nasolacrimal duct obstruction (NLDO). This retrospective study aimed to analyse the occurrence and subjective burden of postoperative foreign body sensation (FBS) following DCR using either intubation method.Methods A total of 130 adult patients who underwent DCR with monocanalicular nasolacrimal duct intubation for 3 months via the upper punctum were included. Group 1 (n = 68) received Mini-Monoka, while Group 2 (n = 62) received Monoka (4 mm) intubation. FBS was assessed via a standardised patient questionnaire.Results Mean age was 63.7 years (range 22 – 91) in group 1 and 61.2 years (range 25 – 79) in group 2. The male-to-female ratio was 3.25 : 1 and 4.64 : 1, respectively. Postoperative FBS was reported by 22.1% in group 1 and 40.3% in group 2. Moderate to severe discomfort was reported by 40% and 56% of affected patients, respectively. Logistic regression revealed a significant influence of the stent system (p = 0.024), but not gender (p = 0.617).Conclusion Both stenting systems are associated with postoperative FBS in a considerable proportion of patients. Due to the higher rate of perceived discomfort under Monoka, Mini-Monoka should be preferred whenever anatomically feasible.
Keywords: lacrimal surgery; dacryocystorhinostomy; monocanalicular intubation; Monoka; Mini-Monoka; lacrimal intubation